Factors determining client loyalty to advertising agencies - Bojei, Jamil (Universiti Putra Malaysia Press, 2000)
The advertising agency-client relationship is an important element in maintaining client loyalty. In this regard, the study attempts to explain why a number of clients maintain loyal relationships with their advertising agencies. Loyalty in advertising agency-client relationship is generally determined by such factors as the business environment in which they operate, organizational structure, well developed general policies, compatible interpersonal characteristics, actual account performance, positive attitudes towards suppliers and effective processes involving suppliers. For the study, both telephone interviews and self-administrated questionnaires were used to collect the data. The respondents consisted of personnel within client organizations who are knowledgeable about advertising practices. A final sample of 133 respondents was obtained from the Klang Valley area to represent the advertising industry. The data was analysed using Univariate Descriptive Analysis and Factor Analysis. Descriptive Analysis gave the overall picture about the study. For the factor analysis, 16 factors were extracted that illustrate the advertising agency-client relationship contributing 72.05% of the variance explained, with Cronbach alpha of 0.909 (90.9%), showing the items used were highly reliable. The 16 factors obtained have a good explanatory power with respect to agency-client loyalty which includes performance oriented partnership, client control and agency leadership, formally structured organization, client centereness and market stability, agency management competency,centralized authority, mutuality of interest, compatibility, conflict resolution and co-operation, creativity, interdependence,co-ordination and specialization, low competition and technological change, matured product, continuity and conformity of norms, absence of erratic changes in strategies and objectives, and strong commitment.